An Investigation of Geometric Semantic GP with Linear Scaling - Nadizar, Giorgia (2023)
Nadizar, G., Garrow, F., Sakallioglu, B., Canonne, L., Silva, S., & Vanneschi, L. (2023). An Investigation of Geometric Semantic GP with Linear Scaling. In GECCO’23: Proceedings of the 2023 Genetic and Evolutionary Computation Conference (pp. 1165-1174). Association for Computing Machinery (ACM). https://doi.org/10.1145/3583131.3590418 --- Funding: This work was partially supported by FCT, Portugal, through funding of research units MagIC/NOVA IMS (UIDB/04152/2020) and LASIGE (UIDB/00408/2020 and UIDP/00408/2020). We also wish to thank the SPECIES Society and Anna Esparcia-Alcázar for organizing the SPECIES Summer School 2022, which brought us together and gave us the chance to start this collaboration